The Changing Disturbance Regime in Eastern Canadian Mixed Forests During the 20th Century - Elzein, Tasneem; Arseneault, Dominique; Sirois, Luc; Boucher, Yan (Frontiers in Ecology and Evolution, 2020)
How did the anthropogenic disturbances of the 20th century alter the natural disturbance regime and the tree species composition of the eastern Canadian mixed forests? To answer this question, we reconstructed the 20th century anthropogenic disturbance regime and analysed its impact on modern forest composition using historical and modern forest inventory and map data. Between 1895 and 2005, an equivalent of 144% of the study area has been logged and 19% burned. The logging rotation period has shortened from 152 years in 1895-1935 to 47 years in 1965-2005, due to increased industrial capacity. The fire rotation period decreased from 1668 years in 1895-1925 to 200 years during the peak of human settlement (1925-1955), and then increased to 2925 years in 1955-2005. The geographical progression of anthropogenic disturbances in the landscape has reflected the socio-economic context. During the 20th century, logging moved inland from the margin of the main water courses, reflecting the shift in wood transport from log driving on rivers to the densification of the road network in the second half of the 20th century. Most fires were located at low altitude, close to private lands suggesting ignitions from anthropogenic origins. Fire prone species (poplars) are mostly found within burned areas. Despite these disturbances, forest composition remained relatively stable, suggesting resilience of regional forest ecosystems.